Sosialisasi Pembuatan Nomor Induk Berusaha (NIB) sebagai Dokumen Awal Sertifikasi Halal bagi UMKM - Nalurita, Indah; Pravitri, Kartika Gemma; Karni, Ine; Putri, Destiana Adinda; Awaliyah, Mia (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The perception of Small and Medium Enterprise (UMKM) regarding the complexity of processing the files required for Business Identification Numbers (NIB) and halal certification is a factor in the low enthusiasm of UMKM members in processing these permits. The percentage of UMKM members in Narmada who have NIB permits is 40%, while the percentage of UMKM members who have halal certificates is only 2%. The method of service activities using socialization and discussion is considered quite appropriate for exploring the problems experienced by UMKM, so that they can obtain effective solutions. The socialization activity for making NIB as the initial document for halal certification for UMKM in Narmada is important to carry out as an effort to help simplify the processing of product licensing for UMKM.